Alloy design for additive manufacturing: Continuously reinforced Al-Ce nanocomposites - Alfred Amon; Glenn E. Bean; J.-B. Forien; Thomas Voisin; Joshua A. Hammons; Emily E. Moore; Emrah Simsek; Jibril Shittu; Katherine S. Shanks; Kelly E. Nygren; Aurélien Perron; Ryan Ott; et al. (Materials & Design)
The composition Al-16Ce-1Mg has been developed as a dedicated alloy for processing by laser powder bed fusion (LPBF). Guided by thermodynamic considerations and exploiting the unique conditions during LPBF, the strongly hypereutectic alloy features nm-scale aluminum dendrites reinforced by a continuous intermetallic network. The unique temperature stability of Al-Ce alloys as well as the microstructure topology and scale grant the alloy high strength in as-printed state with excellent thermal stability. The superior mechanical properties of the continuously reinforced nanocomposite were established by comparison with the spheroidized, microstructure of similar scale.